A rapid review of the literature on HIV-related stigmatization and discrimination studies in Malaysia - Mehrabi, Davood; Tamam, Ezhar; Bolong, Jusang; Hassan, Hamisah (Universiti Putra Malaysia Press, 2015)
This study on HIV-related stigmatisation and discrimination was conducted to summarize key findings and identify existing research gaps in this line of research in Malaysia. A search on available online databases yielded 58 documents, but only 25 were eventually included in the review. Searching process was conducted at the end of 2013 to include all previous relevant studies up to this year but not limited to any specific starting date. Eight journal articles and one research report were empirical studies, and hence were the core documents in the analysis. The studies included were synthesised to identify common shared areas that they investigated and make an updated conclusion about the current state of knowledge on HIV-related stigma in Malaysia. Results revealed that the published works mainly focused on knowledge and attitudes toward HIV. Most studies were descriptive and correlation research. Information about self-stigmatisation is limited, while HIV campaigns in some cases instigate fears that HIV kills. HIV-related stigma still remains pervasive in Malaysia and its literature is very limited and underdeveloped. To gain a better understanding of HIV-related stigma, more theoretically driven studies with rigorous research design and method need to be done.